Odpowiedzi

2009-11-02T21:54:13+01:00
X² + 6x + 9 - x + 1 = x² + 5x + 10

x² - 4x +4 +3x + 3 = x² -x + 7

4a² - b² + 2a² + 6ab - 2b² = 6a² - 3b² + 6ab
2009-11-02T22:03:43+01:00
A) (x+3) ^2 - (x-1)=x²+9+6x-x+1=
=x²+10+5x
b) (x-2)^2+(x+1)*3=x²+4-4x+x³+1+3x=
=x²+x³+5-x
c) (2a-b)(2a+b)+ 2(a^2+3ab-b^2)=
=4a²-b²+2a²+6ab-2b²=
=6a²-3b²+6ab
2009-11-02T22:10:46+01:00
A) (x+3) ² - (x-1)=
x²+6x + 9 -x + 1 = x² + 5x + 10

b) (x-2)²+(x+1)*3=
x² - 4x +4 +3x + 3 = x² -x + 7

c) (2a-b)(2a+b)+ 2(a²+3ab-b²)=
4a² - b² + 2a² + 6ab - 2b² = 6a² - 3b² + 6ab